Fighting Against Deforestation: Ecofeminism in Luh Ayu Manik Mas Hero of the Forests - Kusuma Wardhani, Yanuaresti; Pertiwi, Yudhanita; Hardono (MultiTech Publisher, 2024)
Deforestation is a serious threat for all creatures on earth. As its impacts may destroy various sectors, some women concern to the issue of that environmental damage. They bring the spirit of ecofeminism. This paper aims to discuss ecofeminism concept in a pictorial teen story Luh Ayu Manik Mas: Hero of the Forests. Based on its setting, Luh Ayu Manik as the Balinese girl, fights against deforestation and tries to do reforestation in Bali. Her sense of nurturing for environment is inspired by ecofeminism and Balinese environmental values. This analysis uses ecofeminism concept by Vandana Shiva and qualitative methods. The results are that patriarchy tends to triggers deforestation, while as a young lady, Luh Ayu Manik struggles to eradicate deforestation. She proves that woman is able to empower herself to fight against patriarchy that harm the environment.